2020
DOI: 10.1002/pd.5802
|View full text |Cite
|
Sign up to set email alerts
|

Fetal spina bifida: What we tell the parents

Abstract: Worldwide, about 150 000 infants are born with spina bifida yearly, making this condition one of the most common fetal central nervous system anomalies compatible with life. Over the last decade, major changes have been introduced in the prenatal diagnosis and management of spina bifida. In this review, we provide a brief summary of the current management of fetal spina bifida and present essential information that should be provided to expecting parents when their fetus has been diagnosed with spina bifida. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 91 publications
(161 reference statements)
0
23
0
Order By: Relevance
“…Another strength is that this study provides a first in‐depth exploration of parental experience of fetal surgical SB repair focussing on the acceptability of the intervention, and thereby supports the provision of patient‐centred care 45‐47 . Two recent studies describing the information recommended to counsel parents whose fetus has SB did not address the patient perspective, or did so to a limited extent 48,49 . However, this study has several limitations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another strength is that this study provides a first in‐depth exploration of parental experience of fetal surgical SB repair focussing on the acceptability of the intervention, and thereby supports the provision of patient‐centred care 45‐47 . Two recent studies describing the information recommended to counsel parents whose fetus has SB did not address the patient perspective, or did so to a limited extent 48,49 . However, this study has several limitations.…”
Section: Discussionmentioning
confidence: 94%
“…[45][46][47] Two recent studies describing the information recommended to counsel parents whose fetus has SB did not address the patient perspective, or did so to a limited extent. 48,49 However, this study has several limitations. We only had access to women referred for potential surgery at two centres managed by identical surgical teams.…”
Section: Strengths and Limitationsmentioning
confidence: 93%
“…The impact of this on postnatal neurodevelopmental outcome is currently unclear 19 . Indeed, most children with spina bifida have (close to) normal neurodevelopment and are able to attend regular schooling 20 . Adverse developmental outcomes have nevertheless been identified in those with associated brain anomalies or anomalies of the corpus callosum [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Prior to choosing prenatal or postnatal MMC surgery patients typically go through extensive counseling. 4,5 Although previous research has delineated the risks and benefits of these procedures, many families also consider non-medical factors when making medical decisions. Previous studies have suggested that families consider their religious/spiritual beliefs, finances, family values and planning, support systems, and ability to care for the infant long term prior to physician consultation.…”
Section: Introductionmentioning
confidence: 99%